Intensive Insulin Titration with Insulin Glargine in Insulin-Naive Type 2 Diabetic Patients in Turkey: LANTIT Study - Ercan Tuncel (Turkish Journal of Endocrinology and Metabolism, 2015)
Purpose: This open-label, single-arm, phase 4 study was designed to evaluate the efficacy of intensive insulin glargine titration in type 2 diabetes mellitus (T2DM) patients for 6 months to reach good glycaemic control. Material and Method: Two hundred-forty one insulin-naive T2DM patients were included. The primary efficacy variable was the glycaemic control (HbA1c level of ≤7%). The secondary variables were a fasting blood glucose (FBG) level of <100 mg/dL, the final dose of basal insulin, number of dose adjustments, time to dose titration in reaching target HbA1c level of ≤7%, weight gain and treatment satisfaction using the Diabetes Treatment Satisfaction Questionnaire (DTSQ). Hypoglycemia, severe hypoglycemia and adverse events were also assessed. Results: The mean (±SD) HbA1c level of 8.8±0.6% at baseline decreased to 7.4±0.9% on day-90 (p<0.001) and to 7.3±0.9% on day-180 (p<0.001). The percentage of patients with HbA1c≤%7 was 36.9% on day-90 and 40% on day-180. The mean FBG of 186.3±52.5 mg/dL at baseline decreased to 111.5±36.6 mg/dL on day-90 (p<0.001) and to 114.1± 34.8 mg/dL on day-180 (p<0.001). The mean insulin glargine dose on the last day of FBG measurement (day-89) was 32.7±15.5 IU and the mean number of titrations was 12.7±6.6. These values on day-179 were 36.8±19.4 IU and 5.8±5.7, respectively. The total DTSQ score (20.3±7.7) and scores for each item at baseline showed improvement on day-180 (p<0.001). The most frequently reported adverse reactions were hypoglycaemia (49.7%) and weight gain (9.5%). Serious hypoglycaemia cases reported during the first and the second 3-month periods were 11.2% and 13.3%, respectively. Discussion: In conclusion, the use of insulin glargine with intensive dose titration is effective and safe in T2DM patients. Turk Jem 2015; 19: 83-88